E-EDUCATION IN ACADEMIC ENVIRONMENT - DEDIC, Velimir; RANKOVIC, Marko; ANDELIC, Svetlana; MITIC, Branislav (Annals of Spiru Haret University. Economic Series, 2019)
This paper discusses the major features of e-learning systems used by higher education institutions. A short historical overview provides the necessary perspectives and introduces the subjects of distance learning and e-learning. Major system features are further analyzed and concepts of content personalization and system standardization are given as technical constructs. Elements of further possibilities are displayed at the conclusion of this paper.